Variant ALK-fusion positive anaplastic large cell lymphoma (ALCL): A population-based paediatric study of the NHL-BFM study group - Luedersen, Jette; Stadt, Udo Zur; Richter, Julia; Oschlies, Ilske; Klapper, Wolfram; Rosenwald, Andreas; Kalinova, Marketa; Simonitsch-Klupp, Ingrid; Siebert, Reiner; Zimmermann, Martin; Qi, Minyue; Nakel, Jacqueline; et al. (British journal of haematology, 2024)
Frequency, distribution and prognostic meaning of ALK-partner genes other than NPM1 in ALK-positive anaplastic large-cell lymphoma (ALCL) are unknown. Forty-nine of 316 ALCL diagnosed in the NHL-BFM study group showed no nuclear ALK expression suggestive of a variant ALK-partner; 41 were analysed by genomic capture high-throughput sequencing or specific RT-PCRs. NPM1::ALK was detected in 13 cases. Among the 28 patients with a non-NPM1::ALK-fusion partner, ATIC (n = 8; 29%) and TPM3 (n = 9; 32%) were the most common. Five of eight patients with ATIC::ALK-positive ALCL relapsed, none of nine with TPM3::ALK. Variant ALK-partners are rare and potentially associated with different prognoses.
Keywords: anaplastický velkobuněčný lymfom; Lymphoma, Large-Cell, Anaplastic; Male; Child, Preschool; Anaplastic Lymphoma Kinase; tropomyosin; Adolescent; prognóza; Infant; Child; ALK positive ALCL; dítě; variant ALK; jaderné proteiny; mužské pohlaví; fúzní onkogenní proteiny; anaplastická lymfomová kináza; mladiství; předškolní dítě; non‐Hodgkin's lymphoma; Nucleophosmin; Oncogene Proteins, Fusion; lidé; ženské pohlaví; Humans; kojenec; Prognosis; Female; Tropomyosin; nukleofosmin; Nuclear Proteins